Association Between Glycated Hemoglobin and Diabetic Retinopathy in Individuals with Diabetes: A Focus on the Modifying Effect of Ambulatory Blood Pressure - Yang S; Liu H; Liang Y; Wu L; Zheng Q; Wu J (Clinical Interventions in Aging)
Shenglan Yang,1 Hui Liu,2 Yao Liang,3 Lijing Wu,3 Qidong Zheng,3,* Jing Wu1,* 1School of Nursing, Shanghai University of Traditional Chinese Medicine, Shanghai, 201203, People’s Republic of China; 2Clinical Center for Intelligent Rehabilitation Research, Shanghai YangZhi Rehabilitation Hospital (Shanghai Sunshine Rehabilitation Center), School of Medicine, Tongji University, Shanghai, 201600, People’s Republic of China; 3Yuhuan Second People’s Hospital, Zhejiang, 317605, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jing Wu, School of Nursing, Shanghai University of Traditional Chinese Medicine, 1200 Cai Lun Road, Shanghai, 201203, People’s Republic of China, Tel +86 138 1755 6859, Email allydata@126.com Qidong Zheng, Yuhuan Second People’s Hospital, No. 77, Environmental Protection Middle Road, Yuhuan, Taizhou City, Zhejiang Province, 317605, People’s Republic of China, Tel +8613867682688, Email yuzqd@126.comBackground: Suboptimal glycemic control in individuals with diabetes is one of the major contributors to the development of diabetic retinopathy (DR). However, the role of ambulatory blood pressure (ABP) in this association remains unclear. The purpose of this research was to assess the associations among ABP, glycosylated hemoglobin (HbA1c), and DR in a diabetic population, with an emphasis on individuals exhibiting suboptimal glycemic and BP control.Methods: This study included 498 diabetic patients with comprehensive ABP data. The assessment of diabetes is based on the criteria of the American Diabetes Association (ADA). We adopted Least Absolute Shrinkage and Selection Operator (Lasso) regression to identify key variables and used logistic regression to investigate associations, followed by subgroup analyses.Results: After adjustment for covariance variables, HbA1c showed a strong correlation with DR (OR: 1.228, 95% CI: 1.010– 1.368). Among participants with low ABP, the prevalence of DR rises significantly with higher HbA1c levels (OR: 1.217,95% CI:1.057– 1.402), whereas in those with elevated ABP (OR:1.366,95% CI:1.122– 1.662), this relationship was markedly stronger, particularly in the context of Awake systolic blood pressure (SBP). Comparable findings were noted in both categorical models, as well as in subgroup analyses. However, heterogeneity was observed in subgroup analyses stratified by age.Conclusion: ABP may modify the relationship between HbA1c and DR; specifically, suboptimal glycemic management in patients at elevated ABP levels exacerbates the risk of DR. Therefore, it is imperative for diabetic patients to prioritize both BP regulation and glycemic management in their comprehensive disease management strategy.Keywords: glycosylated hemoglobin, ambulatory blood pressure, diabetic retinopathy, diabetic population